2008
DOI: 10.1007/s00220-008-0566-6
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Entropy in Quantum Spin Chains with Finite Range Interaction

Abstract: We study the entropy of entanglement of the ground state in a wide family of onedimensional quantum spin chains whose interaction is of finite range and translation invariant. Such systems can be thought of as generalizations of the XY model. The chain is divided in two parts: one containing the first consecutive L spins; the second the remaining ones. In this setting the entropy of entanglement is the von Neumann entropy of either part. At the core of our computation is the explicit evaluation of the leading … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 24 publications
4
81
0
Order By: Relevance
“…For simplicity we reduce to the case n = 2; the procedure used here is equivalent to the one used by Its, Jin and Korepin in [25] and generalized by Its, Mezzadri and Mo in [26]. Suppose we want to solve the factorization problem W(t; z) := exp ξ(t, Λ) W(z) = T − (t; z)T + (t; z) for our GD symbol with W(z) = diag(w 1 (z), w 2 (z)) as in example 6.10; since it will appear many times we denote A the matrix…”
Section: Proposition 62 ([23])mentioning
confidence: 99%
See 4 more Smart Citations
“…For simplicity we reduce to the case n = 2; the procedure used here is equivalent to the one used by Its, Jin and Korepin in [25] and generalized by Its, Mezzadri and Mo in [26]. Suppose we want to solve the factorization problem W(t; z) := exp ξ(t, Λ) W(z) = T − (t; z)T + (t; z) for our GD symbol with W(z) = diag(w 1 (z), w 2 (z)) as in example 6.10; since it will appear many times we denote A the matrix…”
Section: Proposition 62 ([23])mentioning
confidence: 99%
“…Asymptotics of block Toeplitz determinants and their applications to physics is a developing field of research; in recent years it has been shown how to compute some physically relevant quantities (e.g. correlation functions) studying asymptotics of some block Toeplitz determinants (see [25], [26], [27]). In particular in [25] and [26] authors, for the first time, showed effective computations for the case of block Toeplitz determinants with symbols that do not have half truncated Fourier series.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations